Smin-gliṅ Rdor-sems sgrub skor - Gter-bdag-gliṅ-pa ʼGyur-med-rdo-rje, 1646-1714 (s.n., 1972)
Ritual and meditational texts focussing upon the contemplation of Vajrasattva; from the Lhoter rites of the Nyingmapa sect of Tibetan Lamaism.